Investigasi Kecepatan dan Jarak Nozel Proses Sandblasting Terhadap Kekasaran Permukaan pada Baja Karbon Rendah - Harmoko Harmoko; Risal Ngizudin (Universitas Batanghari Jambi, 2023)
Sandblasting is a method for cleaning metal surfaces such as rust, oil, dust, and other impurities and for obtaining surface roughness by spraying abrasive materials using a compressor. The aim of the research is as an alternative to cleaning the metal surface and to get the surface roughness of low-carbon steel. This research used variations in sandblasting speed at 60 mm/minute, 120 mm/minute and 180 mm/minute and the nozzle spacing was 10 cm, 15 cm, and 20 cm. Surface roughness testing using Surface Roughness. The results showed that the sandblasting speed of 120 mm/minute had the highest surface roughness of 3.57 Âµm and the lowest surface roughness at the sandblasting speed of 180 mm/minute of 2.99 Âµm. Whereas in the variation of the sandblasting nozzle spacing, the sandblasting nozzle spacing of 15 cm has the lowest surface roughness and the sandblasting nozzle spacing of 20 cm has the highest roughness value. So that the sandblasting speed and nozzle spacing influence the surface roughness of low-carbon steel.